Atomic layer deposited oxide films as protective interface layers for integrated graphene transfer. (6th November 2017) - Cabrero-Vilatela, A; Alexander-Webber, J A; Sagade, A A; Aria, A I; Braeuninger-Weimer, P; Martin, M-B; Weatherup, R S; Hofmann, S
Abstract: The transfer of chemical vapour deposited graphene from its parent growth catalyst has become a bottleneck for many of its emerging applications. The sacrificial polymer layers that are typically deposited onto graphene for mechanical support during transfer are challenging to remove completely and hence leave graphene and subsequent device interfaces contaminated. Here, we report on the use of atomic layer deposited (ALD) oxide films as protective interface and support layers during graphene transfer. The method avoids any direct contact of the graphene with polymers and through the use of thicker ALD layers (≥100 nm), polymers can be eliminated from the transfer-process altogether. The ALD film can be kept as a functional device layer, facilitating integrated device manufacturing. We demonstrate back-gated field effect devices based on single-layer graphene transferred with a protective Al2 O3 film onto SiO2 that show significantly reduced charge trap and residual carrier densities. We critically discuss the advantages and challenges of processing graphene/ALD bilayer structures.